Unveiling Classroom Assessment Literacy: Does Teachers' Self-Directed Development Play Out? - Ling Gan; Ricky Lam (MDPI AG, 2024)
Ideally, teachers' classroom assessment literacy can be developed through in-service teacher education or assessment training from institutions. Yet in reality, teachers may not gain sufficient assessment training on the job or from institutionalised training programmes. This contextual disadvantage cannot explain teacher inertia in advancing their professional knowledge and their skills in classroom-based assessment. Instead, teachers are encouraged to proactively rely on themselves to enhance their CAL amid their tried-and-tested assessment practices. The current qualitative case study explores how a university English teacher directed herself to develop CAL in her assessment practices over time. Data were collected through narrative frames, interviews with the teacher and her students, classroom observations, and documents. This study shows that self-directed CAL development may be buttressed by the teacher's prior assessment experiences. The teacher's self-agency and reflections further empowered her to acquire the assessment knowledge, skills, and experience in improving assessment effectiveness. The implications for enhancing self-directed professional development in assessment are also discussed.